Translation Analysis: Syntactic, Semantic, and Pragmatic Strategies Used in Translating A Website of an Academic Institution - Muhammad Ridha Anugrah Latief; A.ST.Aldilah Khaerana; Andi Inayah Soraya (Hasanuddin University, 2022)
This research aims to discover the emerging translation strategies and the types of translation strategies most frequently used on a website of an academic institution. In finding the data, the researcher employs the descriptive qualitative method by applying the translation strategy theory proposed by Andrew Chesterman in the form of syntactic, semantic, and pragmatic strategies on a website of an academic institution such as the Universitas Hasanuddin website. There are 11 emerging translation strategies on the website; 4 Syntactic Strategies (Literal, Loan/Calque, Transposition, and Phrase Structural Change), 4 Semantic Strategies (Synonymy, Hyponymy, Distribution Change, and Pharaprase), and 3 Pragmatic Strategies (Explicitness Change, Information Change, and Transediting). The result shows that the most frequently used translation strategy is Syntactic Strategies (Literal 60% or 44 data, Loan/Calque 23% or 17 data, Transposition 8% or 6 data, and Phrase Structural Change also 8% or 6 data). Then the second one is Semantic Strategies (Synonymy 7% or 1 datum, Hyponymy 7% or 1 datum, Distribution Change 64% or 9 data, and Pharaprase 21% or 3 data), and last is Pragmatic Strategies (Explicitness Change 8% or 1 datum, Information Change 85% or 11 data, and Transediting 8% or 1 datum).